Doubly Fed Induction Generator Robust Design for Avoiding Converter-Driven Instability: Perspective - Elena Sáiz-Marín; Mohammad Ebrahim Zarei; Diego Medina; Óscar Curbelo; Almudena Muñoz Babiano; Alberto Berrueta; Alfredo Ursúa; Pablo Sanchis (Energies)
Renewable power generation has experienced significant global deployment, leading to the replacement of synchronous generators, which traditionally defined the slow dynamics of power systems. As a result, stability issues related to converter dynamics are becoming increasingly prominent. It is crucial for the grid system to be sure that the renewable generation is robust with regard to the converter dynamics to avoid instability issues. This paper focuses on enhancing wind farm robustness to minimize the risk of converter-driven stability phenomena, considering both grid-feeding and grid-forming control schemes. Three software solutions to improve the stability criteria at the wind turbine level are evaluated, assessing their impact on system performance across various frequency ranges. Additionally, a second solution at the plant level, separate from the software solutions, is also included in the scope of the paper. Moreover, a trade-off analysis was carried out to evaluate these different solutions. Finally, the results showed that the stability criteria can be improved by adopting software solutions without additional costs, but the filter as a plant solution could mitigate the harmonic emission and provide extra reactive power capabilities.